Transcriptome Profile of Yeast Strain Used for Biological Wine Aging Revealed Dynamic Changes of Gene Expression in Course of Flor Development - Mardanov, Andrey V.; Eldarov, Mikhail A.; Beletsky, Alexey V.; Tanashchuk, Tatiana N.; Kishkovskaya, Svetlana A.; Ravin, Nikolai V. (Frontiers in Microbiology, 2020)
Flor strains of Saccharomyces cerevisiae are principal microbial agents responsible for biological wine aging used for production of sherry-like wines. The flor yeast velum formed on the surface of fortified fermented must is a major adaptive and technological characteristic of flor yeasts that helps them to withstanding stressful winemaking conditions and ensures specific biochemical and sensory oxidative alterations typical for sherry wines. We have applied RNAseq technology for transcriptome analysis of an industrial flor yeast strain at different steps of velum development over 71 days under experimental winemaking conditions. Velum growth and maturation was accompanied by accumulation of aldehydes and acetales. We have identified 1490 differentially expressed genes including 816 genes upregulated and 674 downregulated more than 2-fold at mature biofilm stage as compared to the early biofilm. Distinct expression patterns of genes involved in carbon and nitrogen metabolism, respiration, cell cycle, DNA repair, cell adhesion, response to various stresses were observed. Many genes involved in response to different stresses, oxidative carbon metabolism, high affinity transport of sugars, glycerol utilization, sulfur metabolism, protein quality control and recycling, cell wall biogenesis, apoptosis were induced at the mature biofilm stage. Strong upregulation was observed for FLO11 flocculin while expression of other flocculins remained unaltered or moderately downregulated. Downregulated genes included those for proteins involved in glycolysis, transportation of ions, metals, aminoacids, sugars, indicating repression of some major transport and metabolic process at the mature biofilm stage. Presented results are important for in-depth understanding of cell response elicited by velum formation and sherry wine manufacturing conditions, and for the comprehension of relevant regulatory mechanisms. Such knowledge may help to better understand the molecular mechanisms that flor yeasts use to adapt to winemaking environments, establish the functions of previously uncharacterized genes, improve the technology of sherry- wine production, and find target genes for strain improvement.